2017
DOI: 10.1021/acs.macromol.6b02495
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structure, Conformation, and Dynamics of Ring and Linear Poly(ethylene oxide) Melts from Detailed Atomistic Molecular Dynamics Simulations: Dependence on Chain Length and Direct Comparison with Experimental Data

Abstract: We present results from very long (on the order of several microseconds) atomistic molecular dynamics (MD) simulations for the density, microscopic structure, conformation, and local and segmental dynamics of pure, strictly monodisperse ring and linear poly­(ethylene oxide) (PEO) melts, ranging in molar mass from ∼5300 to ∼20 000 g/mol. The MD results are compared with recent experimental data for the chain center-of-mass self-diffusion coefficient and the normalized single-chain dynamic structure factor obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 51 publications
12
77
1
Order By: Relevance
“…Our conjecture is therefore that τ 1 and τ 2 are associated with the fast loop relaxation dynamics and the slower loop migration mechanism, respectively. Atomistic simulations have also shown [20] that the saturation times for loop dynamics increase substantially with the M w of the ring, which is fully consistent with the differences observed in the values of τ 1 and τ 2 between R-2k and R-5k melts. Another important remark is that the three individual characteristic relaxation times τ 1 , τ 2 and τ 3 exhibit an almost quadratic dependence on M w .…”
Section: Systemsupporting
confidence: 81%
See 2 more Smart Citations
“…Our conjecture is therefore that τ 1 and τ 2 are associated with the fast loop relaxation dynamics and the slower loop migration mechanism, respectively. Atomistic simulations have also shown [20] that the saturation times for loop dynamics increase substantially with the M w of the ring, which is fully consistent with the differences observed in the values of τ 1 and τ 2 between R-2k and R-5k melts. Another important remark is that the three individual characteristic relaxation times τ 1 , τ 2 and τ 3 exhibit an almost quadratic dependence on M w .…”
Section: Systemsupporting
confidence: 81%
“…We further hypothesize that the two faster relaxation modes (i = 1 and i = 2) are related to the early time motion of the loops formed by small segments along the ring molecule as, e.g., is visualized by the lattice animal picture model [28,29]). Indeed, SANS measurements [30] validated by MD simulations [20] have revealed that at short times the dynamics of rings are governed by the internal relaxation dynamics of such loops, while at intermediate time scales loop migration prevails. At times on the order of the Rouse relaxation time, these contributions get saturated, and the translational motion of the entire molecule starts dominating ring dynamics [30].…”
Section: Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations and later measurements have uncovered another surprise about ring melts quantified by the mass scaling exponent ν for the radius of gyration, R g . The “Flory theorem,” stating that polymers in the melt are nearly “ideal,” in the specific sense that they should have similar excluded volume (EV) interactions as polymers at their theta point, i.e., ν = 1/2, simply does not hold for ring melts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the PEO is technically important in many fields. As one consequence, various PEO systems (including melts, solutions, blends, and composites) have been extensively studied using AA MD simulations. In particular, I have previously simulated glass transition behaviors of various PEO systems (bulks, films, and isolated chain), validating the employed force field .…”
Section: Computational Detailsmentioning
confidence: 99%